Modulating sphingosine 1-phosphate receptor signaling skews intrahepatic leukocytes and attenuates murine nonalcoholic steatohepatitis - Liao, Chieh-Yu; Barrow, Fanta; Venkatesan, Nanditha; Nakao, Yasuhiko; Mauer, Amy S.; Fredrickson, Gavin; Song, Myeong Jun; Sehrawat, Tejasav S.; Dasgupta, Debanjali; Graham, Rondell P.; Revelo, Xavier S.; Malhi, Harmeet (Frontiers in Immunology, 2023)
Sphingosine 1-phosphate (S1P) is a bioactive sphingolipid associated with nonalcoholic steatohepatitis (NASH). Immune cell-driven inflammation is a key determinant of NASH progression. Macrophages, monocytes, NK cells, T cells, NKT cells, and B cells variably express S1P receptors from a repertoire of 5 receptors termed S1P1 – S1P5. We have previously demonstrated that non-specific S1P receptor antagonism ameliorates NASH and attenuates hepatic macrophage accumulation. However, the effect of S1P receptor antagonism on additional immune cell populations in NASH remains unknown. We hypothesized that S1P receptor specific modulation may ameliorate NASH by altering leukocyte recruitment. A murine NASH model was established by dietary feeing of C57BL/6 male mice with a diet high in fructose, saturated fat, and cholesterol (FFC) for 24 weeks. In the last 4 weeks of dietary feeding, the mice received the S1P1,4,5 modulator Etrasimod or the S1P1 modulator Amiselimod, daily by oral gavage. Liver injury and inflammation were determined by histological and gene expression analyses. Intrahepatic leukocyte populations were analyzed by flow cytometry, immunohistochemistry, and mRNA expression. Alanine aminotransferase, a sensitive circulating marker for liver injury, was reduced in response to Etrasimod and Amiselimod treatment. Liver histology showed a reduction in inflammatory foci in Etrasimod-treated mice. Etrasimod treatment substantially altered the intrahepatic leukocyte populations through a reduction in the frequency of T cells, B cells, and NKT cells and a proportional increase in CD11b+ myeloid cells, polymorphonuclear cells, and double negative T cells in FFC-fed and control standard chow diet (CD)-fed mice. In contrast, FFC-fed Amiselimod-treated mice showed no changes in the frequencies of intrahepatic leukocytes. Consistent with the improvement in liver injury and inflammation, hepatic macrophage accumulation and the gene expression of proinflammatory markers such as Lgals3 and Mcp-1 were decreased in Etrasimod-treated FFC-fed mice. Etrasimod treated mouse livers demonstrated an increase in non-inflammatory (Marco) and lipid associated (Trem2) macrophage markers. Thus, S1P1,4,5 modulation by Etrasimod is more effective than S1P1 antagonism by Amiselimod, at the dose tested, in ameliorating NASH, likely due to the alteration of leukocyte trafficking and recruitment. Etrasimod treatment results in a substantial attenuation of liver injury and inflammation in murine NASH.